Air quality monitoring system using LoRa sensor and IoT - Tuan Ahmad Luqman, Tuan Khahiril Annuar (2022)
Now that technology has advanced Air Quality Monitoring of air components in the air radius covered by the gas sensors. The objective is to make the system work off the grid. While PM2.5 and PMl 0 particulate matter is not measured, this project focuses on the other constituents of air pollutants like Carbon Monoxide, Ground - Level Ozone, Carbon Dioxide and also temperature and humidity readings. These readings are taken using sensors such as MQ-131, MQ-7, MQ-135 and DHT 220 Each sensor detects ground level ozone, carbon monoxide and smoke/C02 including temperature and humidity data respectively. These data are then processed by the Arduino determining its current API reading and sending the data to another node be it the front sensor node or the gateway node. If the receiving node is a sensor node, it too will take its local readings due to its similar exact design with the other sensor nodes with its own set of exact same sensors and then proceeds to forward both sets of data towards a gateway node which connects to the internet through GPRS using a SIM800L module and connecting to ThingsBoard demo Io T platform to monitor the sensor readings.